Manajemen Informasi Keuangan, Sentimen Pasar, dan Reputasi Emiten dalam Strategi Pengambilan Keputusan Investasi oleh Investor Institusional di Bursa Efek Indonesia - Fernanda, Olivia; Tasrim, Tasrim (Journal of Management and Bussines (JOMB), 2025)
This study aims to understand the investment decision-making strategies of institutional investors on the Indonesia Stock Exchange, emphasizing three main aspects: financial information management, market sentiment, and issuer reputation. The research method used is a descriptive qualitative approach, with data collected through documentation and non-participatory observation from credible online sources, followed by thematic analysis. The results indicate that investment decisions are not solely determined by conventional financial indicators but are also significantly influenced by market perception and company reputation. Financial information serves as the basis for objective evaluation, market sentiment influences asset allocation preferences, and issuer reputation is a differentiating factor in assessing long-term investment viability. The study's conclusions confirm that these three factors form a complementary ecosystem of information and perception, making institutional investment decisions a complex process that demands data accuracy, responsiveness to sentiment, and reputation consistency.   Keywords: Institutional Investment, Financial Information, Market Sentiment, Issuer Reputation